Les bouleversements de la vie économique de Najaf et leurs incidences sociales (1923-1958) - Thibaud Laval (Les Cahiers d’EMAM)
By tracing the main upheavals in the economic history of the Shiite holy city of Najaf, Iraq, between 1923 and 1958, this article analyzes their immediate effects on the social and urban development of the city and on the shifting of its visible and invisible boundaries. The main economic crises affecting Najaf include the interruption of the pilgrimage, the Great Depression of 1929, the British occupation of Iraq in 1941, and climatic hazards. The article focuses in particular on the development of overpopulation, unemployment, hunger, and crime in Najaf and the means employed by the authorities to respond to these social issues. In particular, it shows that urban expansion and the modernization of infrastructure are helping to transform the traditional social practices of this holy city and are profoundly changing its internal boundaries.